Pengaruh Debt to Equity Ratio terhadap Return On Equity pada UD. Yusman Sibuluan Kabupaten Tapanuli Tengah - Muti Arlisna; Nur’Ainun Hasibuan; Jeniusman Ahmad Hutagalung (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of Debt to Equity Ratio (DER) on Return on Equity (ROE) at UD. Yusman Sibuluan, Central Tapanuli Regency. The research uses a quantitative approach with a descriptive associative method. The data used are secondary data in the form of financial statements for the period 2020–2024, analyzed using simple linear regression with the assistance of SPSS. The results show that DER has a negative relationship with ROE, with a correlation coefficient of -0.123 and a coefficient of determination of 1.5%. The regression equation obtained is Y = 2.429 – 0.369X. Hypothesis testing indicates that DER has no significant effect on ROE, with a significance value of 0.844 (>0.05). Therefore, it can be concluded that DER is not a major factor affecting ROE at UD. Yusman Sibuluan, while the remaining variation is influenced by other factors outside this study.